Annual Plan 1993-94 Volume-V General Areas Government of Assam - Planning Commission (Planning Commission, 1993)
In the draft annual Plan, 1992-93 a sum of Rs.131.65 Crore was proposed as against of which the working group has also recommended an outlay of Rs. 131.35 Crore. But in course of final allocation, the amount has been reduced to Rs. 75.40 Crore. Subsequently, an additional allocation of Rs. 10.00 Crore has been agreed to With the said additional amount the total allocation will come to Rs. 93.40 Crore.
Government of Assam, Planning and Development Department